1993
DOI: 10.1111/j.1439-037x.1993.tb00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Residual Effect of Different Organic Fertilizers on Potato and Cereals

Abstract: Field experiment with 8 different organic fertilizers (cattle dung with and without litter, pig slurry, peat compost formed from hen and pig slurry, sawdust-duck manure, noncomposted peat and straw litter with pig slurry) was carried out on loamy brown podzoluvisol since 1985.The organic fertilizers were applied in the spring of 1985 on two backgrounds: with and without mineral fertilizers. The material is based on the data of four years (1985)(1986)(1987)(1988). The arrangement of crops was the following: pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The discrepancy in the findings may be due to the heterogeneity of the physical and chemical characteristics of the different organic fertilizers, which may give rise to different yields even under the same crop conditions. This was shown by comparison of eight types of organic fertilizers (Kanal and Kuldkepp, 1993), which included cattle dung with and without litter, pig slurry, peat compost formed from hen and pig slurry, sawdust-duck manure, non-composted peat and straw litter with pig slurry applied to potato and cereal crops. The findings of that study indicate that the results obtained with different types of organic fertilizers are not readily comparable, and thus a specific agronomic evaluation is required for each type of organic fertilizer, crop and type of management.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy in the findings may be due to the heterogeneity of the physical and chemical characteristics of the different organic fertilizers, which may give rise to different yields even under the same crop conditions. This was shown by comparison of eight types of organic fertilizers (Kanal and Kuldkepp, 1993), which included cattle dung with and without litter, pig slurry, peat compost formed from hen and pig slurry, sawdust-duck manure, non-composted peat and straw litter with pig slurry applied to potato and cereal crops. The findings of that study indicate that the results obtained with different types of organic fertilizers are not readily comparable, and thus a specific agronomic evaluation is required for each type of organic fertilizer, crop and type of management.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning Ca content, the obtained data show that there is no consistent trend in calcium content between different treatments including the control in both seasons. Organic manures enhanced soil properties and soil fertility (Mathew and Karikari, 1995) and (Kaurch et al, 2005) and might lead to the increase of available nutrients and their uptake (Kanal and Kuldkepp, 1993). The addition of organic manure might have provided supplemental exchangeable actions such as potassium, calcium, magnesium and ammonium as well as increasing the available phosphorous (Magdoff, 1998 andOfosu-Anim et al, 2006).…”
Section: Fruit Qualitymentioning
confidence: 99%
“…Tirol- Padre et al (2007) reported that the organic manure may be beneficial to both the soil and crop in the long term. Moreover, Kanal & Kuldkepp (1993), Mottaghian et al (2008) and Aisueni et al (2009) showed that, generally, the organic manure used in combination with mineral fertilizers to improve crop growth and yield in the short term, although Kassem & Marzouk (2002) and Marzouk & Kassem (2011) showed that organic manure alone improved the fruit quality, nutritional value, and yield of Flame Seedless grapes (Vitis vinifera L.) and Zaghloul dates (Phoenix dactylifera L.), respectively. Moreover, organic manure uses improved soil organic matter and soil nutrients, which were released slowly and steadily and were efficiently used during later growth stages of crop (Baghdadi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%